ANALISIS PENGARUH HALAL AWARENESS DAN HALAL CERTIFICATION TERHADAP MINAT BELI PRODUK MAKANAN KORINUS TOK-POKI (Studi Pada Mahasiswa Muslim Pecinta Drama Korea) - Rafika Tri Cahya; Nur Diana; Harun Alrasyid (Universitas Islam Malang, 2022)
The Korean Wave phenomenon entered Indonesia through halal food diplomacy suchas k-pop and k-drama. This has led to high consumer buying interest in Korean food. Thisstudy aimed to determine the effect of halal certification and halal awareness on the purchaseintention of Korinus TOK-POKI food products. The population in this study are Muslimstudents who love Korean dramas and are interested in buying and have purchased HalalTok-Poki (Korinus Tok-Poki) products in Malang City. The sample used in this study was 74respondents who had met the sampling criteria. The analytical method used is multiple linearregression, instrument test, descriptive analysis, normality test, classical assumption test, andhypothesis testing. The results of this study indicate that partially halal certification has apositive and significant effect on buying interest; partially, halal awareness has a positiveand significant effect on buying interest. Moreover, halal certification and awareness affectthe interest in buying Korinus TOK-POKI food products.